Pediatric Abdominal Tuberculosis in Singapore: A 10-Year Retrospective Series - Sarah Ailyne Wong MBBS, MRCPCH, MMED (Paeds); Dawn Lee Meijuan MBBS, MRCPCH, MMED (Paeds); Sin Wee Loh MBBS, MRCPCH, MMED (Paeds); Koh Cheng Thoon MBBS, MRCPCH (UK); Natalie Woon Hui Tan MBBS (Spore); Chia Yin Chong MBBS, MMed (Paeds) (SAGE Publishing, 2020)
Background . Tuberculosis (TB) remains a major cause of mortality and morbidity globally. Pediatric patients are more likely to develop severe disease. Abdominal TB is a rare manifestation of pediatric TB and can present with chronic and nonspecific abdominal symptoms. This study examines the clinical profile of pediatric patients with abdominal TB and treatment outcomes. Method . A retrospective study of patients admitted to a tertiary pediatric hospital in Singapore over 10 years. Clinical characteristics and outcomes were examined. Results. There were 3 male and 3 female patients with mean age of 11.3 years. Household contacts were traced in 3 cases. The most common presenting symptoms were fever, weight loss, and abdominal symptoms such as diarrhea, vomiting, and loss of appetite. Inflammatory markers were raised with mean C-reactive protein (CRP) and erythrocyte sedimentation (ESR) rate at 70.9 mg/L and 90 mm/h respectively. Abdominal imaging showed abnormalities such as splenic foci and thickened bowel wall with significant intraabdominal lymphadenopathy. Mycobacterium tuberculosis was isolated from stool, rectal swabs and intra-adominal specimens. Two patients underwent excisional biopsy of lymph node to obtain diagnosis. Two patients required emergency laparotomy and 1 patient received esophagogastroduodenoscopy and colonoscopy. Four out of the 6 patients had pulmonary involvement. Conclusion . Abdominal TB should be a differential diagnosis in children with chronic abdominal symptoms for at least 8 weeks with anemia, raised ESR and CRP. The gold standard for diagnosis still remains as positive microbiological culture. However, abdominal imaging studies are also vital in obtaining further supportive evidence for chronic infection.